The presence of risk factors in the home environment that influences the fall of people of the third age - Ratko Zlatičanin; Amila Jaganjac; Arzija Pašalić; Amra Mačak Hadžiomerović (Journal of Health Sciences)
Introduction: Aging is a natural, irreversible physiological process that depends on genetic, environmental, and lifestyle factors. Many physiological, biological, psychological, and other factors play a major role. According to the World Health Organization, falls are the second leading cause of unintentional injury death in the world and represent a major global public health problem. Falls are most commonly caused by intrinsic and extrinsic risk factors. A comprehensive assessment of fall risk is critical to the development of effective fall prevention programs. The screening protocol is brief, easy to use, and multifactorial and allows the identification of risk factors for falls. The aim of this study is to investigate the importance of the presence of risk factors in the home environment and the impact on increasing the risk of falls in people in the third age.